2012
DOI: 10.3109/14653249.2011.651529
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived mesenchymal stromal cells from genetically modified pigs: immunogenicity and immune modulatory properties

Abstract: Background aims The immunomodulatory and anti-inflammatory effects of mesenchymal stromal cells (MSC) could prove to be a potential therapeutic approach for prolongation of survival of cell xenotransplantation. Adipose (Ad) MSC from genetically modified pigs could be an abundant source of pig donor-specific MSC. Methods Pig (p) MSC were isolated from adipose tissue of α1,3-galactosyltransferase gene knock-out pigs transgenic for human (h) CD46 (GTKO/ hCD46), a potential source of islets. After characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
0
26
0
2
Order By: Relevance
“…Transplant of cells derived from another species [55], [56], another organism of the same species [57], seemingly inappropriate tissue origin [58], biochemically damaged/modified [59] and even genetically transfected cells [60] have all been attempted despite the developmental organisational hurdles believed by so many others [61]. The concept of ‘pluripotency’ has been heralded despite the consequences of potential teratomas [62].…”
Section: Discussionmentioning
confidence: 99%
“…Transplant of cells derived from another species [55], [56], another organism of the same species [57], seemingly inappropriate tissue origin [58], biochemically damaged/modified [59] and even genetically transfected cells [60] have all been attempted despite the developmental organisational hurdles believed by so many others [61]. The concept of ‘pluripotency’ has been heralded despite the consequences of potential teratomas [62].…”
Section: Discussionmentioning
confidence: 99%
“…For example, pigs expressing the immunoregulatory molecule CTLA4-Ig have been produced [24] [25], and anti-inflammatory agents have been shown to reduce the human T cell response to pig cells in vitro [16]. Our previous studies indicated that a large number of MSC can be effectively harvested from GTKO/CD46 pig fat tissue [26]. We have also shown that Gal expression was associated with increased human T cell responses to pig cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…73 When delivered in the absence of a scaffold, galactosyl epitope knock-out (Gal-KO) pig MSCs attenuated immune response and improved bone regeneration. 68,106 This strategy could serve to improve the host response to native ECM scaffolds. Allogenic and xenogenic ECM materials, even after decellularization, are capable of eliciting an immune response due to the presence of ECM proteins, which have been shown to stimulate the migration of neutrophils and macrophages.…”
Section: Biological Propertiesmentioning
confidence: 99%